Given the equation:
\[ -h - k = j \]
We can manipulate this equation to find out which of the provided equations must also be correct.
-
Start with the original equation: \[ -h - k = j \]
-
We can isolate \( j \) by multiplying the entire equation by -1: \[ h + k = -j \]
This is equivalent to: \[ -j = h + k \]
Analyzing the proposed answers:
-
−j = h − k:
- This is not correct since we found \( -j = h + k \), not \( h - k \).
-
−j = −h k:
- This is not correct because it does not correspond to the derived equation.
-
j = hk:
- This is also not correct. We do not have a relation that corresponds to \( j \) being equal to \( h \) over \( k \).
-
−j = −h − k:
- Rearranging the equation gives us \( -j = -(h + k) \). This simplifies to \( -j = -h - k \), which is equivalent to our derived form.
Conclusion:
The only correct equation from the given responses is:
- −j = −h − k.
So, the correct response is:
−j = −h − k.